Developing scripted video cases for teacher education: Creating evidence-based practice representations using mock ups - Seidel, Tina; Farrell, Meg; Martin, Monika; Rieß, Werner; Renkl, Alexander (Frontiers in Education, 2022)
Video cases are commonly used in teacher education to support evidence-based professional knowledge acquisition. Novice teachers, however, often struggle when learning with video, since they lack professional knowledge schemata that facilitate noticing and reasoning about relevant events. Scripted video case development provides an approach to make relevant events more salient and visible. In alignment with previously reported approaches, we applied relevant design steps and quality criteria within the presented project to promote use in further research. Thereby, we introduce the novel approach of using mock-up settings as a way to identify naturalistic behavior as a basis for script development. User experience (UX) evaluations based on defined quality criteria of realistic experiences (i.e., authenticity), personal relevance (i.e., utility value), engagement (i.e., situational interest), and challenge (i.e., cognitive load) were carried out in a set of four studies including N = 423 teacher students. Findings support the conclusion that our design approach resulted in the development of high-quality scripted video cases for further use in initial teacher education.